Role of IL-37 and Dectin-1 during Toxoplasmosis (Baghdad Science Journal, 2023)
Toxoplasmosis is a parasitic infection that triggers immune cells to produce cytokines and inflammatory mediators that are responsible for abnormal or aborted immune responses. This study highlights the evaluation of the Dectin-1 receptor and cytokine IL-37 in the serum of 80 patients who had miscarried in the first trimester and were infected with toxoplasmosis, as well as 40 pregnant women in the first trimester who had a successful pregnancy (control groups). The serum was first screened for the T. gondii IgM and IgG antibodies by an enzyme-linked immunosorbent assay (ELISA) and then the serum levels of IL-37 and Dectin-1 were determined. The results showed that the serum level of Dectin-1 was significantly increased in anti-Toxoplasma IgM and IgG patients 362.382 ± 45.937 and 361.916 ± 71.993 ng/L respectively, as compared with the controls 155.702 ± 26.356 ng/L, while the serum level of IL-37 was convergent in anti-Toxoplasma IgM and IgG patients and controls 52.666 ± 4.272, 66.808 ± 9.132, and 51.984 ± 3.619 ng/L respectively, with no significant differences. In conclusion, Dectin-1 receptor may play a role in pregnancy loss, especially in T. gondii infection.